2020
DOI: 10.1177/1533033820956988
|View full text |Cite
|
Sign up to set email alerts
|

High SENP3 Expression Promotes Cell Migration, Invasion, and Proliferation by Modulating DNA Methylation of E-Cadherin in Osteosarcoma

Abstract: SENP3, a sentrin/SUMO2/3-specific protease, is recognized as a transcriptional factor that accumulates under cellular oxidative stress and plays a significant role in the removal of SUMO2/3 modification. In our study, we examined a TCGA dataset and found that the transcripts per million (TPM) value of SENP3 is high in sarcoma, including osteosarcoma (OS). We found that SENP3 was highly expressed in OS cancer tissues when compared with osteofibrous dysplasia tissues. The survival data of SENP3 in TCGA showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…In mice, the deletion of SENP3 in macrophages promotes breast cancer progression and metastasis, according to recently published studies. Moreover, SENP3 may also promote cancer progression by regulating macrophage polarization ( 32 ), and high SENP3 levels are associated with more advanced tumor grades and metastasis as well as poor survival outcomes ( 33 ), meaning that SENP3 may play a role in tumorigenesis and progression. However, the function of SENP3 in TNBC is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…In mice, the deletion of SENP3 in macrophages promotes breast cancer progression and metastasis, according to recently published studies. Moreover, SENP3 may also promote cancer progression by regulating macrophage polarization ( 32 ), and high SENP3 levels are associated with more advanced tumor grades and metastasis as well as poor survival outcomes ( 33 ), meaning that SENP3 may play a role in tumorigenesis and progression. However, the function of SENP3 in TNBC is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…DNA methylation of tumor-suppressing genes is also facilitated directly by other proteins in OS. SENP3, a sentrin/SUMO2/3-specific protease, is upregulated in OS and associated with reduced expression of E-Cadherin (E-Cad) mRNA [ 25 ]. Yang et al demonstrated that the E-cad promoter region featured abnormal methylation of CpG islands in OS patient samples.…”
Section: Methylationmentioning
confidence: 99%
“…Mechanistically, overexpressed SENP3 in GC cells targets the EMT-inducing transcription factor forkhead box C2 (FOXC2) for desumoylation, which, in turn, activates expression of the EMT-associated and transendothelial migration-promoting N-cadherin gene ( CDH2 ), among others. In relation to this, it has also been shown that SENP3 overexpression in osteosarcoma cells results in inhibited expression of the epithelium-associated gene CDH1 , which courses with promoter hypermethylation [ 122 ]. Database analysis indicates that in general SENP3 is abundantly expressed in sarcoma and high expression correlates with poor prognosis, being shown in osteosarcoma that SENP3 depletion results in impaired proliferation, migration and invasion, and in enhanced apoptosis.…”
Section: Sumo Proteases In Cancermentioning
confidence: 99%
“…Database analysis indicates that in general SENP3 is abundantly expressed in sarcoma and high expression correlates with poor prognosis, being shown in osteosarcoma that SENP3 depletion results in impaired proliferation, migration and invasion, and in enhanced apoptosis. Thus, SENP3 has been suggested as a powerful biomarker for osteosarcoma diagnosis [ 122 ]. SENP3 , in combination with ARID1A and CSMD has also been proposed as an effective prognosis marker in HCC, despite molecular heterogeneity detected in HCC patients [ 118 ].…”
Section: Sumo Proteases In Cancermentioning
confidence: 99%